“And the soul came in a whirlwind”: Oral narratives about the dead who return and the discourses of Andean migrant resistance - Angulo Villán, Florencia Raquel (2021)
Despite the ethnic hostility discourses, different manifestations of Andean culture are incorporated into the annual socio-cultural practicesin San Salvador de Jujuy city in Argentina. This article will discuss a selection of oral accounts narrated by informants from the region toshow “cultural plasticity” (Mamani Macedo, 2019, p. 13) with which Andean migrant subjects incorporate their own knowledge into urban discourse.The reading hypothesis is that oral accounts of returning dead people, souls or ghosts are constructed by words/images that make upsemantic images of cultural resistance. These oral accounts refer to the Andean universe over, and over again, subverting the official stories and the modernity/coloniality discourses.